Program Living Qur’an Pada Program Magrib Mengaji Masjid Muslimin - Limbong, Isman Effendi (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the implementation, contribution, and sustainability of the Living Qur’an program within the Magrib Mengaji activities at Masjid Muslimin, Medan City, as a means of shaping Qur’anic character among children and adolescents. Using a qualitative phenomenological approach, this research explores the experiences of teachers, participants, parents, and mosque administrators in enlivening Qur’anic values through activities of reading, understanding, and practicing the teachings of the Qur’an in daily life. The findings indicate that the Magrib Mengaji program not only focuses on the technical ability to read the Qur’an but also emphasizes the internalization of moral and social values such as discipline, responsibility, and compassion. The synergy between teachers, mosque administrators, and parents serves as a key factor in the program’s success. Furthermore, the sustainability of the program is supported by structured management, resource availability, and active community participation. Despite challenges such as attendance fluctuation and limited contextual learning materials, value-based learning innovations and socio-religious activities have strengthened the mosque’s role as a center for Qur’anic character education. Theoretically, this study contributes to the development of a community-based Living Qur’an concept, while practically providing a sustainable model of non-formal religious education within the mosque environment.